Development of an innovative halal logistics concept for the air cargo supply chain - Yvonne Ziegler; Vincenzo Uli; Astrid Kramer; Mahmoud Tatari (Frankfurt University of Applied Sciences, Fachbereich 3: Wirtschaft und Recht, 2021)
The aim of this paper, which is positioned within the research domain of logistics and supply chain management, is to present a holistic perspective on the development of an innovative halal air cargo supply chain. To the best of our knowledge, a fully integrated halal supply chain "from farm to fork" represents a complete novelty, especially in the context of a non-Muslim-dominant country such as Germany. As a matter of fact, although some major European seaports have been certified according to halal standards (i.e. Rotterdam in 2007, and Zeebrugge and Marseille in 2012), they are still unable to guarantee the integrity of halal products across the entire supply chain. The seven chapters into which this paper is organised address the various aspects of a halal supply chain. After the introduction (Chapter 1) and the definition of the concept of halal (Chapter 2), we analyse the demand side (Chapter 3) and the supply side (Chapter 4) of the halal market. In the last three chapters, we provide a view of the current halal logistics requirements (Chapter 5), develop a fully compliant halal air cargo process (Chapter 6) and, finally, provide conclusions and empirical suggestions for the implementation of this process (Chapter 7). [...] – – Das Ziel dieser im Forschungsbereich Logistik und Supply Chain Management angesiedelten Arbeit ist es, einen ganzheitlichen Ansatz für die Entwicklung einer innovativen Halal-Luftfracht-Lieferkette zu entwickeln. Nach dem Stand aktuellen Forschung ist eine voll integrierte Halal-Lieferkette "From farm to fork" bisher noch nicht implementiert, erst recht nicht in einem nicht-muslimisch geprägten Landes wie Deutschland. Es sind zwar einige große europäische Seehäfen nach Halal-Standards zertifiziert (z.B. Rotterdam 2007, Zeebrugge und Marseille 2012), aber sie sind aber noch nicht in der Lage, die Integrität von Halal-Produkten über die gesamte Lieferkette zu garantieren. Im Rahmen der sieben Kapitel dieser Arbeit werden die verschiedenen Aspekte einer Halal-Lieferkette vorgestellt. Nach der Einleitung (Kapitel 1) und der Definition des Konzepts von Halal (Kapitel 2) folgt eine Analyse der Nachfrage- (Kapitel 3) und Angebotsseite (Kapitel 4) von Halalprodukten in Deutschland. In den letzten drei Kapiteln geben wir einen Überblick über die aktuellen Halal-Logistikanforderungen (Kapitel 5), entwickeln einen vollständig konformen Halal-Luftfrachtprozess (Kapitel 6) und geben schließlich Empfehlungen für die Umsetzung dieses Prozesses (Kapitel 7). [...]
Keywords: 330